Modiolus (Modiolus) nipponicus ... - Lutaenko, K. A.; Kepel, A. A. (Zenodo, 2017)
Modiolus (Modiolus) nipponicus (Oyama, 1950) Рис. 1C–F; 2C Modiolaria semigranata (Reeve, 1858): Yokoyama, 1924, p. 53, pl. 3, fig. 14. (non Reeve, 1858). Volsella traillii (Reeve, 1857): Nomura, Hatai, 1935, p. 7 (non Reeve, 1857). Volsella nipponica Oyama, 1950, p. 1. Volsella (Volsella) nipponica Oyama, 1950: Habe, 1951, p. 50; Ichikawa, 1983, p. 523. Volsella agripeta Iredale, 1939: Kuroda, Habe, 1952, p. 35 (non Iredale, 1939). Modiolus nipponicus (Oyama, 1950): Kuroda, 1957. p. 28; Yamamoto, Habe, 1958, p. 8, pl. 4, fig. 11; Kira, 1959, p. 116, pl. 45, fig. 16; Horikoshi, 1960, p. 11; Ito, 1967, p. 65; Habe et al., 1986, p. 27;? Lee, Morton, 1985, p. 59, pl. 4, fig. D; Kim, Choe, 1988, p. 374; Fukuda et al., 1992, p. 83, pl. 27, fig. 446a, b; Huang, 1994, p. 390; Shell of Toyama City…, 1994, p. 47; Kanzaemon Kikuchi’s Shell Collection, 1997, p. 81; Nakaba Tachibana’s Shell Collection, 1999, p. 62; Okutani, 2000, p. 867, pl. 431, fig. 19; Kubota, Koyama, 2002, p. 135; Hylleberg, Kilburn, 2003, p. 144; ... : Published as part of Lutaenko, K. A. & Kepel, A. A., 2017, Finding of Modiolus nipponicus (Oyama, 1950) (Bivalvia: Mytilidae) in Russian waters of the Sea of Japan, pp. 163-177 in The Bulletin of the Russian Far East Malacological Society 21 (1 / 2) on pages 165-171, DOI: 10.5281/zenodo.12775371 ...